2012
DOI: 10.1038/jhg.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous mutation in SPINK5 exon 11 causes Netherton syndrome by altering exonic splicing regulatory elements

Abstract: Netherton syndrome (NS) is a rare, life-threatening ichthyosiform syndrome caused by recessive loss-of-function mutations in SPINK5 gene encoding lymphoepithelial Kazal-type-related inhibitor (LEKTI), a serine protease inhibitor expressed in the most differentiated epidermal layers and crucial for skin barrier function. We report the functional characterization of a previously unrecognized synonymous variant, c.891C4T (p.Cys297Cys), identified in the SPINK5 exon 11 of an NS patient. We demonstrated that the c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In SPINK5 gene, the relatively frequent synonymous c.891C>T transition induces E11 skipping causing NS. Its molecular mechanism, simply based on bioinformatics analysis was previously attributed to the disruption of an SRSF1-dependent ESE [Fortugno et al, 2012;Lacroix et al, 2012]. In this work, to better understand the pathological splicing event affecting E11 in the presence of the +9T mutation and to provide a mutation-specific correction strategy, we performed detailed binding and functional analysis of splicing factors and evaluated a novel ExSpe U1-based therapeutic approach for splicing correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SPINK5 gene, the relatively frequent synonymous c.891C>T transition induces E11 skipping causing NS. Its molecular mechanism, simply based on bioinformatics analysis was previously attributed to the disruption of an SRSF1-dependent ESE [Fortugno et al, 2012;Lacroix et al, 2012]. In this work, to better understand the pathological splicing event affecting E11 in the presence of the +9T mutation and to provide a mutation-specific correction strategy, we performed detailed binding and functional analysis of splicing factors and evaluated a novel ExSpe U1-based therapeutic approach for splicing correction.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70 loss-of-function mutations have been described in SPINK5 [Lacroix et al, 2012]. One of these, the c.891C>T (p.Cys297Cys) synonymous variant within exon 11 (E11), is the most frequent mutation in NS patients of European origin [Fortugno et al, 2012;Lacroix et al, 2012]. This mutation leads to out-of-frame exon skipping and was suggested to disrupt an SRSF1dependent ESE [Lacroix et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…All other point mutations in gene coding sequences are usually scored as missense, nonsense or silent mutations. However, exonic mutations altering mRNA splicing have been described in several genetic disorders including neurofibromatosis, type 1 (OMIM #162200), cystic fibrosis (OMIM #219700), ataxia telangiectasia (OMIM #208900), familial breast–ovarian cancer (OMIM #604370) and Netherton syndrome (OMIM #256500) . The present data further underline the importance of RNA analysis and full gene screening in the molecular analysis of typical phenotypes for which no mutations are found in routinely screened regions.…”
Section: Reportmentioning
confidence: 57%
“…[10] hypothesized that p.Cys297Cys is fully penetrant, Fortugno et al . [11] showed that p.Cys297Cys also does not cause complete abolishing of natural splice sites and partial expression of LEKTI1 is preserved [11]. …”
Section: Discussionmentioning
confidence: 99%